PTH-118 Challenges and Solutions for Nurse Training Upon The Introduction of Multiple Novel Therapeutic Endoscopic Procedures in A Tertiary Endoscopy Unit. (17th August 2016) - McPeake, C; Prendergast, J; McLoughlin, H; Donald, S; Kennedy, K; Walsh, L; Sarkar, S; Shaw, C; O'Toole, P; Smart, H; Jayapal, R
Abstract : Introduction: In 2015 we introduced 5 new therapeutic procedures endoscopic procedures in the Royal Liverpool University Hospital. Namely; Per- Oral –Endoscopic- Myotomy (POEM), STRETTA (radiofrequency coagulation of the lower esophageal sphincter and gastroesophageal junction, Ampullectomy, Necrosectomy and Lower GI Endoscopic Submucosal Dissection. The introduction of one new procedure to our large endoscopy workforce could have been deemed as challenging with the comprehensive teaching and training involved; so the initiation of 5 may be regarded as chaotic. To counteract this, the planning and management of the staff training and informed participation in the four procedures needed to be timely, efficient and focused with the establishment of a structured plan. The objective was to initiate all five new endoscopy techniques by establishing a safe and competent nursing workforce through an effective training programme. Methods: In 2015 the Sisters on the endoscopy Unit were made aware of the 5 procedures to be implemented that year. Early recognition that appropriate training inputs were needed was key. It was decided that we dedicate a lead nurse (Band 6) alongside a core group of 2 staff nurses to be trained firstly in each of the five areas. This would allow for development of a small but highly knowledgeable practitioners, confident to assist with the endoscopy before dissemination to all staff. The lead nurse created DOPs forms alongside the Consultant lead for the particular procedure. This was used as competency framework and uploaded onto our local GIN programme. We organised equipment demonstrations and training from the Reps of the particular equipment to be used per procedure. In-house endoscopy education breakfast meetings was used as an ideal forum to get staff engagement and broaden their knowledge base. Good communication between endoscopy staff led to clear plans and unified organisation of processes. Core staff were given weekly dedicated planning time to talk through the process of the day of planned procedure; order of events, gaining familiarity with equipment, discussions of pre and post procedure protocols and precautions and the opportunity to address any queries, worries and concerns. Communication with entire endoscopy workforce regarding to what the core staff would be doing on the day of procedure and how it would be organised was continuous to maintain confidence and clarity. Results: Patient information sheets for each procedure were developed with nurse lead and the consultants and agreed by the Trust patient group forum. All 5 procedures were completed successfully in 2015:- 1 POEM procedure, 1 Stretta procedure, 4 Ampullectomy, 3 lower GI ESD and 15 Necrosectomy procedures. Feedback from staff regarding their preparation for admitting, intra-procedure and post procedure deemed that their training needs were met. Comments included:- "I feel privileged to be trained in the new procedures like POEM. I don't think many other hospitals in the UK do this procedure so having the training on my CV makes me stand out""Having the rep's from the STRETTA equipment talk through what was involved helped me feel reassured. I realised that the training I have received so far on this department has enabled me to now become adaptable to new procedures in a short space of time""I asked Dr. all my queries and anxieties about necrosectomy in advance of assisting in the procedure. In that way, I felt confident in what I was doing. I had a clear plan pre, intra and post procedure for my patients and it made the experience enjoyable and now I am training others using the DOPs forms we have created". Conclusion: The consensus is that the identification and training of a core group before dissemination lead to expertise being developed by a small number of staff. This competence and knowledge helped other staff to have expert "go-to" endoscopy nurses that they would be trained by and have DOP assessment. The creation and standardisation via the DOPs forms means they can be used for years ahead. What may seem as daunting new procedures for some endoscopy nurses is now broken down to step by step guidance and the forms can be used to continually assess until competence is gained. Disclosure of Interest: None Declared